THE SZEKLERS AND HUNGARIANS FROM ROMANIA - Gr.P. POP; A. NIŢĂ (Studia Universitatis Babeş-Bolyai: Geographia, 2015)
The Szeklers and Hungarians from Romania. This study regards, as its main topic, the possibility of establishing at present, a geodemographical entity on Romania’s territory, since certain representatives of the Hungarian ethnical minority in our country, and with a particular insistence of those in the vicinity of the western border, always remember to bring into view the problem of establishing an autonomy, common to a Székely Land, located in the central area of our country, which would include Mureş, Harghita and Covasna counties. Without carrying out a detailed account of this situation, it needs to be mentioned, just as it will emerge of the following presentation, that such an approach has neither the most reduced geodemographical support, since the Szeklers, after being assimilated by the Hungarian ethnic group, are no longer present at the census of 20 October 2011. By taking into account the above mentioned aspects, in order to be able to respond to the insistent requests for autonomy in Transylvania, we proceeded to highlight, through a fairly detailed approach of the Hungarian ethnical minority, obviously in point of the number of inhabitants and of their distribution on Romania’s territory, resulting of this the fact that the number of Hungarians is of 1,227,623 people, value which related to those 20,121,641 inhabitants of Romania, means 6.10%. The total number of mentioned Hungarians is characterized by a pronounced concentration on Romania’s territory, standing out by creating a corridor with a diagonal aspect, on the northwest-southeast direction, consisting of seven counties, the first four (Satu Mare, Bihor, Sălaj and Cluj) being registered with 2.01% (404,561 inhabitants) of those 6.10% Hungarians, the following three (Mureş, Harghita and Covasna) accounting for 3.03% (609,033 inhabitants), and hence in the corridor are present 5.04% (1,013,594 Hungarians) of 6.10% at the level of the entire country. The above mentioned corridor is surrounded by a ring of 11 counties (Maramureş, Bistriţa-Năsăud, Suceava, Neamţ, Bacău, Vrancea, Buzău, Braşov, Sibiu, Alba and Arad), in which there are only 0.76% (153,397 people) of the Hungarians living in Romania, while in the other 18 counties and Bucharest municipality, the Hungarian ethnic group enrolls only with 0.30% (60,632 people) at national level (Table 7).